Hepatocyte Nuclear Factor-1β Controls Mitochondrial Respiration in Renal Tubular Cells - Casemayou, Audrey; Fournel, Audren; Bagattin, Alessia; Schanstra, Joost; Belliere, Julie; Decramer, Stéphane; Marsal, Dimitri; Gillet, Marion; Chassaing, Nicolas; Huart, Antoine; Pontoglio, Marco; Knauf, Claude; et al. (Journal of the American Society of Nephrology, 2017)
AKI is a frequent condition that involves renal microcirculation impairment, infiltration of inflammatory cells with local production of proinflammatory cytokines, and subsequent epithelial disorders and mitochondrial dysfunction. Peroxisome proliferator-activated receptor γ coactivator 1- α (PPARGC1A), a coactivator of the transcription factor PPAR- γ that controls mitochondrial biogenesis and function, has a pivotal role in the early dysfunction of the proximal tubule and the subsequent renal repair. Here, we evaluated the potential role of hepatocyte nuclear factor–1 β (HNF-1 β ) in regulating PPARGC1A expression in AKI. In mice, endotoxin injection to induce AKI also induced early and transient inflammation and PPARGC1A inhibition, which overlapped with downregulation of the HNF-1 β transcriptional network. In vitro , exposure of proximal tubule cells to the inflammatory cytokines IFN- γ and TNF- α led to inhibition of HNF-1 β transcriptional activity. Moreover, inhibition of HNF-1 β significantly reduced PPARGC1A expression and altered mitochondrial morphology and respiration in proximal tubule cells. Chromatin immunoprecipitation assays and PCR analysis confirmed HNF-1 β binding to the Ppargc1a promoter in mouse kidneys. We also demonstrated downregulation of renal PPARGC1A expression in a patient with an HNF1B germinal mutation. Thus, we propose that HNF-1 β links extracellular inflammatory signals to mitochondrial dysfunction during AKI partly via PPARGC1A signaling. Our findings further strengthen the view of HNF1B -related nephropathy as a mitochondrial disorder in adulthood.